2015
DOI: 10.1111/iwj.12430
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vacuum‐assisted closure therapy on the wound healing process in cardiac surgery

Abstract: Postoperative deep sternal wound infection (DSWI) is a serious complication in cardiac surgery (1-5% of patients) with high mortality and morbidity rates. Vacuum-assisted closure (VAC) therapy has shown promising results in terms of wound healing process, postoperative hospital length of stay and lower in-hospital costs. The aim of our retrospective study is to report the outcome of patients with DSWI treated with VAC therapy and to assess the effect of contributory risk factors. Data of 52 patients who have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“…Gdalevitch et al [107] found that positive blood cultures, wound depth of ≥ 4 cm, and high degree of bony exposure and sternal instability are significant predictors of NPWT failure. Pericleous et al [108] highlighted also the importance of lung emphysema, corticosteroids, and advanced age. Finally, Gustafsson et al [109] stressed bacteremia or elevated plasma C-reactive protein levels as the most sensitive predictors of failure.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…Gdalevitch et al [107] found that positive blood cultures, wound depth of ≥ 4 cm, and high degree of bony exposure and sternal instability are significant predictors of NPWT failure. Pericleous et al [108] highlighted also the importance of lung emphysema, corticosteroids, and advanced age. Finally, Gustafsson et al [109] stressed bacteremia or elevated plasma C-reactive protein levels as the most sensitive predictors of failure.…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…Regarding the methodological delineations found, six (75%) were retrospective observational studies, and two (25%) cohort studies. [10][11][12][13][14][15][16][17] Six articles have similar methodological characteristics, being A1, A2, A3, A4, A5, and A8 retrospective observational studies, and two (A6 and A7) retrospective cohort studies. The analysis of the results showed three therapies used in the treatment of mediastinitis after cardiac surgery, being: Negative Pressure Wound Therapy (NPWT), also known as vacuum assisted therapy; conventional treatment; and drainage by closed system.…”
Section: /16mentioning
confidence: 99%
“…The analysis of the results showed three therapies used in the treatment of mediastinitis after cardiac surgery, being: Negative Pressure Wound Therapy (NPWT), also known as vacuum assisted therapy; conventional treatment; and drainage by closed system. [10][11][12][13][14][15][16][17] adjusted in -125 mmHg versus conventional dressing (chlorhexidine or paraffin). Infection: in the conventional group, eight patients required surgical review for reinfections.…”
Section: /16mentioning
confidence: 99%
See 2 more Smart Citations